Mixed-Use Building Design Apartments And Commercial Building - Edward Shobari; Kemal Affandi; Nutrian Galupamudia (Program Studi Arsitektur Fakultas Sains dan Teknik (F-INTEN), 2022)
By 2020, the 2,444,160 projected population of Bandung will continue to grow, as the need for housing in Bandung City is increasing, but the land is available for restricted housing. Congestion is a problem that needs to be solved as well too. This traffic was caused by a sizable Bandung movement, especially with the movement intent to work at 60.55%. To solve this problem, mixed buildings can be an alternative solution. The mixed-use building contained a vertical dwelling that increased land efficiency, and there is also a diversity of functions that can reduce movement. By choosing new urbanism themes, the entire design aspect of the mixed-use building is linked to 10(ten) new urbanism principles, such as material, public space, circulation, and landscape.